Nurses Barriers to Evidence-Based Practice in Palliative Care: A Systematic Review - Falah Jamal Dakka (SAGE Publishing, 2022)
Background Research shows low evidence-based practice (EBP) uptake among palliative care nurses, a global concern because the demand for palliative care services is rising, raising the urgent need to improve healthcare quality. Promoting EBP uptake in palliative care can improve healthcare quality. This systematic review investigated nurses' barriers to EBP implementation in palliative care. Methods PubMed, MEDLINE, CINHAL, and Google Scholar were used to identify seven articles. Articles were included for review if they were published within the past 10 years (English only) and investigated barriers to EBP implementation in palliative care. Results Four barriers were identified: (a) time and resource constraints, (b) lack of readiness for organizational change, (c) negative attitudes toward palliative care, and (d) process-specific difficulties. Conclusion This systematic review's findings can inform policy changes to improve the uptake of EBP in palliative care.